Minimally Invasive Multidisciplinary Approach to Chronic Giant Inguinoscrotal Hernias. (August 2019) - Sanford, Zachary; Weltz, Adam S.; Singh, Devinder; Hanley, Robert; Todd, David; Belyansky, Igor
Background . Giant inguinoscrotal hernias (GIH) are defined as groin hernias extending below the mid-thigh when standing, often significantly encumbering activities of daily living. To date, there are no reports utilizing the combination of progressive pneumoperitoneum (PPP), botulinum toxin A injection (BTI), and enhanced view-totally extraperitoneal (eTEP) technique for GIH repair. In this report, we present 2 such cases of this unique minimally invasive multidisciplinary approach to address GIH. Series Presentation . Two individuals with lifelong complaints of GIH presented for elective hernia repair, each with significant morbidity relating to their pathology and profound loss of abdominal domain. Four weeks prior to surgery, BTI was administered to the lateral abdominal compartment muscles to facilitate regional paralysis, followed by PPP to develop larger intraabdominal domain. Utilizing the eTEP access technique and transversus abdominis release, a wide retromuscular dissection was performed to aid in the increase of intraabdominal domain and to develop a large space for mesh placement. Reconstruction including partial scrotectomy and scrotoplasty using adjacent tissue transfer technique was completed. Both patients tolerated the procedures well without recurrence in the first postoperative year. Conclusion. In this article, we present the first series of GIH patients undergoing combined PPP, BTI, and eTEP access approach to retromuscular dissection. This multidisciplinary approach to patient care has proven both safe and effective.